The Effect of Lime Addition on Consistency and Maximum Stress in Silt-Clay Soil - Risayanti; Farni, Indra; Zufrimar (Civil Engineering Collaboration, 2026)
Silty–clayey soils with moderate to high plasticity often present geotechnical problems due to high compressibility, low bearing capacity, and sensitivity to moisture variations. This study aims to evaluate the effect of lime addition on soil consistency characteristics and maximum stress, and to investigate the quantitative relationship between the plasticity index (PI) and maximum stress (qu) as an integrated approach for assessing soil stabilization. Laboratory tests were conducted using lime contents of 0%, 3%, 5%, 7%, and 9% by dry weight of soil. The evaluated parameters included liquid limit (LL), plastic limit (PL), plasticity index (PI), and unconfined compressive strength (UCS). The results indicate that lime addition significantly reduced the plasticity index from 23.13% to 8.89%, accompanied by an increase in maximum stress from 0.119 kg/cm² to 0.291 kg/cm². Regression analysis revealed a strong negative linear relationship between PI and qu, with a coefficient of determination (R²) of 0.98. The optimum lime content was found to be in the range of 5–7%, providing the most efficient combination of plasticity reduction and strength improvement. These findings suggest that the plasticity index has strong potential to be used as a preliminary parameter for estimating strength improvement in lime-stabilized silty–clayey soils during the early stage of ground improvement planning.